A 94 kb Genomic Sequence 3′ to the Murine Xist Gene Reveals an AT Rich Region Containing a New Testis Specific Gene Tsx - Simmler, Marie-Christine; Cunningham, David B.; Clerc, Philippe; Vermat, Thierry; Caudron, Bernard; Cruaud, Corinne; Pawlak, André; Szpirer, Claude; Weissenbach, Jean; Claverie, Jean-Michel; Avner, Philip (Human molecular genetics, 1996)
X chromosome inactivation in both mouse and human requires the presence of a cis acting locus, the X inactivation centre. This locus is thought to be involved in the initiation and spreading of the inactivation signal in early development. In order to increase our understanding of the mouse X inactivation centre, a 94 kb region immediately distal to the Xist gene has been sequenced and analysed for the presence of transcription units and/or potential cis acting regulatory elements. We have identified a novel gene, Tsx, lying 40 kb 3′ from Xist. Tsx is expressed specifically in the testis and shows no convincing homology to proteins currently in the databases. A rat homologue, also X linked, has been isolated. The mouse and rat Tsx sequences are highly divergent, suggesting that part of the X inactivation centre, including both Xist and Tsx are subject to relatively weak evolutionary constraints.